Liberation from Mechanical Ventilation: Established and New Insights - Burns, Karen E.A.; Agarwal, Arnav; Bosma, Karen J.; Chaudhuri, Dipayan; Girard, Timothy D. (Seminars in Respiratory and Critical Care Medicine, 2022)
A substantial proportion of critically ill patients require ventilator support with the majority requiring invasive mechanical ventilation. Timely and safe liberation from invasive mechanical ventilation is a critical aspect of patient care in the intensive care unit (ICU) and is a top research priority for patients and clinicians. In this article, we discuss how to (1) identify candidates for liberation from mechanical ventilation, (2) conduct spontaneous breathing trials (SBTs), and (3) optimize patients for liberation from mechanical ventilation. We also discuss the roles for (4) extubation to noninvasive ventilation and (5) newer modes of mechanical ventilation during liberation from mechanical ventilation. We conclude that, though substantial progress has been made in identifying patients who are likely to be liberated (e.g., through the use of SBTs) and management strategies that speed liberation from the ventilator (e.g., protocolized SBTs, lighter sedation, and early mobilization), many important questions regarding liberation from mechanical ventilation in clinical practice remain unanswered.
Keywords: acute respiratory failure; mechanical ventilation; ventilator support